Classical Music and Anxiety In primigravida mother Trimester III - Wiwin Renny R; Esti Handayani; Sri Winarsih (Jurnal Riset Kesehatan, 2012)
This study aims to determine the different levels of anxiety before and after classical music in the third trimester primigravida pregnant women. The subjects in this study is the first time pregnant women at 28-40 weeks of gestation between the health center located in Magelang regency Mungkid. The sampling technique used was purposive sampling method. Scale refers to pregnant women anxiety scale is Hamilton Anxiety Rating Scale (HARS). This type of research is a quasi-experimental studies, using pre and post test design group. There are differences in levels of anxiety before and after administration of classical music in the third trimester primigravida pregnant women.